2006
DOI: 10.1159/000092016
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Hepatitis B Vaccine in End-Stage Renal Disease Patients

Abstract: Background: This retrospective and comparative study evaluated the relationship between different factors which may contribute to suboptimal immunological response to intramuscular recombinant hepatitis B vaccine in end-stage renal disease (ESRD) subjects. Methods: From a cohort of 64 dialysis subjects undergoing primary vaccination with Engerix-B®, we determined the predictive factors that impinged on patients’ response to vaccine, as defined by anti-HBs level ≧10 mIU/l. Dose efficacy was further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Two hepatitis B infections occurred over the follow-up in 1 trial (21), no SAEs were observed in the others (23)(24)(25)(29)(30)(31). No dropouts due to side effects were reported.…”
Section: Side-effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two hepatitis B infections occurred over the follow-up in 1 trial (21), no SAEs were observed in the others (23)(24)(25)(29)(30)(31). No dropouts due to side effects were reported.…”
Section: Side-effectsmentioning
confidence: 99%
“…A total of 11 studies met the inclusion criteria (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). A complete list of the 431 reports reviewed is available (see supplementary File 2).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding studies not fulfilling inclusion criteria, 19 clinical trials [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] have been remained whose demoKhedmat H et al . Sex and HBV vaccine immunogenicity graphic data is summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%